Failure of Forestry Political Economy of Indonesia - Sudarsono Soedomo (Jurnal Manajemen Hutan Tropika, 2017)
Indonesia's natural forest has been persistently declining, even with the fastest rate in the world, regardless of various efforts to stop the decline or at least to reduce the rate significantly. At the same time, development of plantation forest has been very slow. Amongst the various causes of the natural forest loss that have been identified, financial nonprofitability was not one of them. That being said, the fundamental reason as to why utilization of natural forest for timber production will not survive in the long run is because of financial nonprofitability.   In order for a business to stay in the industry of the natural forest utilization, the government should provide financial incentives using public's money. Hence, the public support for the forestry is vital for the survival of the industry?. However, improper implementation of forestry laws can have damaging impacts to the public's perception and support.   Moreover, the five policies, namely forest land establishment, fees, and royalties, log export ban, certification, and forest management unit establishment, which have failed to deliver sustainable natural production forests, are shortly discussed. Finally, the more appropriate approach of natural forest utilization is basically not as a sustainable forest management but rather as the optimal timber mining, which consequently requires different set of policies.